Staphylococcus nepalensis: A New Species from Nepal - Kripa Ghimire; Rajeshawr Reddy Kasarla (Journal of Universal College of Medical Sciences, 2023)
The Genus Staphylococcus belong to the family Staphylococcaceae which comprise of 53 valid species. These are the normal ﬂora of mucocutaneous membranes of mammals and usually of felines. Staphylococcus nepalensis is one of the member of genus Staphylococcus which show close resemblance to Staphylococcus cohnii, Staphylococcus gallinarum and Staphylococcus succinus. Thus, phenotypic tests are not sufﬁcient to characterize them sufﬁciently, molecular intervention is required for their correct identiﬁcation. In recent times, the cases associated with S. nepalensis is surging and this may create problems as they are seen to be highly resistant towards some of the antibiotics like cefoxitin and penicillin. Their potential to transfer resistant genes to Staphylococcus aureus isolated from human clinical samples via plasmid and their ability to form bioﬁlm are threatening as they may lead to increase in burden of antimicrobial resistance. There may be more cases of infection with S.nepalensis but may have remained hidden due to limited number of research. Thus, the knowledge and scientiﬁc information on Staphylococcus nepalensis is still unknown or relatively limited; hence this comprehensive review of S.nepalensis is undertaken to highlight its importance and research.